24. OS Software: an alternative to costly Learning Management Systems - Depow, Jim (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2003)
This is the first in a series of two reports discussing the use of open source software (OSS) and free software (FS) in online education as an alternative to expensive proprietary software. It details the steps taken in a Canadian community college to download and install the Linux Operating System in order to support an OSS/ FS learning management system (LMS).